Pengaruh Kegiatan Ice Breaking terhadap Perkembangan Emosional Anak Usia Dini - Putri krismawati salam, Putri; Chandra Apriyansyah (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
Ice breaking is an activity carried out to train concentration, melt the atmosphere and reduce student boredom in participating in learning activities. The purpose of this study was to find out the effect of ice breaking activities on the emotional development of early childhood. This research was conducted at SPS Baitul Hidayah which is located at Jatikramat Indah 2 Jatikramat Jatiasih, Bekasi City. The sample used in this study were all students in group B, totaling 29 people. The data of this study were obtained from observations based on indicators of children's emotional development. Data analysis using descriptive analysis and hypothesis submission in this study using paired sample te-test. Based on the results of the paired sample t-test, the results of the pretest in the experimental group showed the average score was 19.67, after being given treatment in the form of ice breaking activities, the posttest results on the emotional development of early childhood increased by an average of 35.13. While the results of the pretest in the control group showed an average score of 18.79, after being given treatment there was an increase with an average of 32.57. So it can be concluded that ice breaking activities have an influence on the emotional development of early childhood at Baitul Hidayah SPS in the 2021/2022 school year.